IL‐1α inhibits proliferation and adipogenic differentiation of human adipose‐derived mesenchymal stem cells through NF‐κB‐ and ERK1/2‐mediated proinflammatory cytokines. (15th May 2018) - Sun, Xuerong; Zou, Tangbin; Zuo, Changqing; Zhang, Mingmeng; Shi, Benyan; Jiang, Zhiwen; Cui, Hongjing; Liao, Xiaoxin; Li, Xiaoyi; Tang, Yuelian; Liu, Yusheng; Liu, Xinguang
Abstract: Dysfunctional adipogenesis such as subcutaneous lipoatrophy is closely related to insulin resistance and metabolic disorders. Although the expression or release of the cytokine interleukin‐1α (IL‐1α) is known to increase in adipose tissue in response to cell death, cell senescence, aging, or solar radiation, the regulatory role of IL‐1α in adipogenesis has not been sufficiently investigated. To investigate the problem, we explored the effect of IL‐1α on the proliferation and adipogenic differentiation of human adipose‐derived mesenchymal stem cells (ADSCs) using cell counting, alamarBlue assay, oil red O staining, Western blot, among others. The results showed that IL‐1α evidently inhibited the proliferation and adipogenic differentiation of ADSCs, which might be related with the activated nuclear factor‐κB (NF‐κB) and extracellular signal‐regulated kinase (ERK) 1/2 pathways. Early‐stage adipogenic differentiation was more sensitive to IL‐1α than late‐stage differentiation. After differentiation of ADSCs into mature adipocytes, adding of IL‐1α had no obvious influence on the cellular morphology, including lipid droplet accumulation. IL‐1α enhanced the expression of proinflammatory cytokines, such as IL‐8, IL‐6, CCL2 (C‐C motif chemokine ligand 2), and IL‐1β, when added into the adipogenic medium of ADSCs. Blocking IL‐8 and IL‐6 with neutralizing antibodies partially alleviated the inhibitory effect of IL‐1α on the proliferation and adipogenic differentiation. The results suggest that IL‐1α inhibits adipogenesis through activation of NF‐κB and ERK1/2 pathways and subsequent upregulation of proinflammatory cytokines in ADSCs. IL‐1α might play an important role in mediating lipoatrophy by regulation of ADSCs.